Cancer Immunotherapy: PD‐1 Blockade Cellular Vesicles for Cancer Immunotherapy (Adv. Mater. 22/2018). Issue 22 (May 2018) - Zhang, Xudong; Wang, Chao; Wang, Jinqiang; Hu, Quanyin; Langworthy, Benjamin; Ye, Yanqi; Sun, Wujin; Lin, Jing; Wang, Tianfu; Fine, Jason; Cheng, Hao; Dotti, Gianpietro; et al.
Abstract : In article number1707112, Peng Huang, Zhen Gu, and co‐workers engineer cellular nanovesicles presenting PD‐1 receptors on their membranes, which enhance antitumor response by disrupting the PD‐1/PD‐L1 immune inhibitory axis. These nanovesicles could also be adapted to carry a variety of therapeutics to achieve synergistic cancer therapy.